Soluble expression and sodium channel activity of lt16a, a novel framework XVI conotoxin from the M-superfamily. (May 2015) - Zhou, Maojun; Wang, Lei; Wu, Yun; Liu, Junliang; Sun, Dandan; Zhu, Xiaoyan; Feng, Yuchao; Qin, Mengying; Chen, Shangwu; Xu, Anlong
Abstract: A peptide toxin, lt16a, from the venom of the worm-hunting Conus litteratus, shares the typical signal peptide sequences of M-superfamily conotoxins, which usually contain six cysteine residues that are arranged in a CC-C-C-CC pattern. Interestingly, lt16a comprises 21 amino acid residues in its mature region and has a cysteine framework XVI, which is arranged in a C-C-CC pattern. The coding region of lt16a was cloned into the pTRX vector and the fusion protein was overexpressed in Escherichia coli . After cleaving the fusion protein and purifying the protein lt16a using chromatography, the mass of lt16a was found by mass spectrometry to be consistent with the expected mass of 2357.7 Da. Whole-cell patch clamp experiments demonstrated that lt16a could inhibit both the TTX-sensitive and TTX-resistant sodium currents in adult rat dorsal root ganglion neurons. The inhibition of lt16a on TTX-resistant sodium currents was stronger than on TTX-sensitive sodium currents. To our knowledge, this is the first report of a framework XVI conotoxin that can inhibit voltage-gated sodium channel currents in mammalian sensory neurons. This report helps facilitates an understanding of the sequence diversity of conotoxins. Highlights: We identified a vermivorous conotoxin lt16a with a cysteine framework XVI. lt16a was successfully expressed as a fusion protein with TRX in Escherichia coli . lt16a can inhibit both the TTX-sensitive and TTX-resistant sodium currents.